Uniform infection screening allowed safe head and neck surgery during the coronavirus disease 2019 pandemic in Japan. (13th October 2020) - Ito, Akiko; Kobayashi, Kenya; Shiotsuka, Mika; Sato, Tetsufumi; Omura, Go; Matsumoto, Yoshifumi; Ikeda, Atsuo; Sakai, Azusa; Eguchi, Kohtaro; Takano, Tomonari; Matsumoto, Fumihiko; Kobayashi, Osamu; et al.
Abstract: Background: The purpose of this study was to determine whether a uniform infection screening protocol could be used to safely perform head and neck cancer surgery during the coronavirus disease 2019 pandemic and clarify how surgical treatment changed compared with the pre-pandemic period. Materials and methods: During the unprecedented coronavirus disease 2019 pandemic in Tokyo, we continued providing head and neck cancer care, guided by our own uniform screening protocol. In this study, medical records of 208 patients with head and neck malignancy, who underwent surgical treatment at our hospital during the first and second wave of pandemic for each 2-month period (first wave: 30 March 2020–30 May 2020, second wave: 14 July 2020–14 September 2020) and the 2-month pre-pandemic period (30 October 2019–30 December 2020), were analysed. Results: A total of 133 patients were admitted for surgical treatment and all, except six patients with emergency tracheostomy, were screened according to the protocol. As a result, all 127 patients received surgical treatment as planned, and all 1247 medical staff members involved in the surgeries were uninfected by severe acute respiratory syndrome coronavirus 2. During the first wave of pandemic, 20% reduction of head and neck surgery was requited; however, restrictions of surgery were not necessary during the second wave. Surgical procedure, length of hospitalization, postoperative complications and number of medical staff were unchanged compared with pre-pandemic period. Conclusion: Our data indicate that continuation of head and neck anticancer surgical treatment in an epidemic area during the coronavirus disease 2019 pandemic were safe and feasible, if adequate and strict preventive measures are vigorously and successfully carried out. Abstract : During the coronavirus disease 2019 pandemic in Tokyo, we could provide safe and efficient head and neck cancer care guided by our own infection screening protocol.